2014
DOI: 10.3109/00498254.2014.973930
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea purpureaup-regulates CYP1A2, CYP3A4 and MDR1 gene expression by activation of pregnane X receptor pathway

Abstract: This study investigated the mechanism underlying Echinacea-mediated induction of CYP1A2, CYP3A4 and MDR1 in terms of human pregnane X receptor (PXR) activation. Crude extracts and fractions of Echinacea purpurea were tested for PXR activation in HepG2 cells by a reporter gene assay. Quantitative real-time PCR was carried out to determine their effects on CYP1A2 and CYP3A4 mRNA expressions. Capsules and fractions were risk ranked as high, intermediate and remote risk of drug-metabolizing enzymes induction bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The immune response of E. purpurea is to combat pathogen infections and enhance the activities of neutrophils, macrophages, poly morphonuclear leukocytes (PMN) and natural killer cells (NK) [ 7 ]. Especially in some African countries, it could have a great effect on treating patients who are infected with HIV [ 8 ]. Clinical trials have demonstrated that E. purpurea can be used for the treatment of cancer or provide a substitute treatment for cancer patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immune response of E. purpurea is to combat pathogen infections and enhance the activities of neutrophils, macrophages, poly morphonuclear leukocytes (PMN) and natural killer cells (NK) [ 7 ]. Especially in some African countries, it could have a great effect on treating patients who are infected with HIV [ 8 ]. Clinical trials have demonstrated that E. purpurea can be used for the treatment of cancer or provide a substitute treatment for cancer patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study showing the effects of an Echinacea preparation and isolated alkylamides on CYP3A4 expression did not document any statistically significant changes in the mRNA steady-state level of CYP3A4 after treating human hepatic cellular carcinoma HepG2 cells with clinically relevant concentrations of Echinaforce ® or any of the alkylamides [133]. Conversely, in the same cell line, positive results were obtained more recently that suggest gene expression up-regulation of metabolic enzyme and transporter by activation of PXR pathway [143,144]. In co-transfected HepG2 cells using the luciferase gene reporter assays, it was observed that Echinacea extract induced a time-and concentration-dependent activation of CYP3A4, CYP1A2 enzymes and the ABCB1 drug transporter [143].…”
Section: Echinaceamentioning
confidence: 92%
“…It is used to treat colds, upper respiratory infections, and dermatologic issues, and contains cichoric acid, caftaric acid, and echinacoside [ 84 , 85 , 86 ]. Crude extracts of Echinacea activate hPXR to induce CYP3A4 gene transcription and increase the mRNA of CYP1A2, CYP3A4, and MDR1 in the HepG2 cell line [ 87 ]. However, Echinacea extract may inhibit the rifampicin-mediated induction of CYP3A4 transcription via hPXR [ 45 ] and has been reported to inhibit CYP1A2 and CYP3A [ 41 , 42 ].…”
Section: Herbal Supplements With Potential P450-associated Hepatotmentioning
confidence: 99%